(untitled) (Przegląd Religioznawczy – The Religious Studies Review, 2024)
In Cieszyn Silesia, since the partition times, various alternative communities have been dynamically developing. Their messages, programs and proposed practices were a response to the unpredictability of everyday life. Their importance clearly increased in times of breakthroughs marked by an intensified feeling of uncertainty (destabilization resulting from World War I, the Polish-Czechoslovak war and the division of Cieszyn Silesia, economic and social changes of the Second Polish Republic, fears related to the upcoming next world war, etc.). These environments crystallized around charismatic leaders who, using various forms of spiritual leadership, reached out with their message to diverse groups of recipients. This paper attempts to present from the perspective of Max Weber’s theory of charisma and Marjorie Garber’s symtomatology, how the leaders of the alternative environment of Cieszyn Silesia (Agnieszka Pilchowa, Kazimiera Chobotowa, Maria Florkowa, Józef Chobot, Andrzej Podżorski, Jan Hadyna) built their authority, formulated models of spiritual guidance on the basis of esoteric worldviews and thus respondend to certain cultural fears and anxieties.